Definisi, Dimensi, Tujuan dan Fungsi dari Evaluasi Kelembagaan Pendidikan Islam - Deli Meylindo; Okta Viani; Ermi Aprilia; Dessy Eka Citra Dewi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Evaluation of Islamic educational institutions is a systematic process to assess the extent to which Islamic educational institutions carry out their functions, achieve their goals, and meet the established quality standards, both in terms of managerial, administrative, and academic aspects. This evaluation not only functions as a performance measurement tool, but also as a means of reflection and continuous improvement in order to improve the quality of education based on Islamic values. The dimensions of institutional evaluation include various important aspects such as the vision and mission of the institution, curriculum, educators, students, community facilities and infrastructure, institutional management, and the relationship between the institution and. The main purpose of this evaluation is to ensure the quality of education, encourage public accountability, and ensure the relevance of the institution to the needs of the times and the demands of Islamic law. In its context, institutional evaluation is not only administrative and technocratic, but also transformative, namely serving to guide institutions in carrying out comprehensive structural and cultural improvements in order to be able to produce generations that excel spiritually, intellectually, and socially.